Stability of sugars in yogurts with simple and complex microbial composition during refrigerated shelf life - Kate Sorensen; Zeynep Atamer; Joy Waite-Cusic (Journal of Dairy Science)
ABSTRACT: There is a large and growing market for natural sweeteners with low glycemic index. Of particular interest are the “rare sugars” (e.g., d-tagatose). Rare sugars could be applied in dairy foods, such as yogurt, as sucrose replacements. Yogurt contains live and active cultures and, consequently, their enzymes. These enzymes include those capable of sugar hydrolysis or isomerization, which could undermine the nutritional benefits of rare sugars. The purpose of this research was to evaluate sugar stability and influence of added sugars during storage of commercial nonfat Greek yogurts having simple and complex microbial compositions. Two commercial nonfat Greek yogurt products with different bacterial profiles (simple: Streptococcus thermophilus and Lactobacillus delbrueckii ssp. bulgaricus; complex: S. thermophilus, L. delbrueckii ssp. bulgaricus, Bifidobacterium lactis, Lactobacillus acidophilus, and Lacticaseibacillus rhamnosus) were supplemented with sugars (fructose, galactose, glucose, lactose, sucrose, and d-tagatose) at 10% (wt/wt) in duplicate and sampled every 2 wk. Individual sugar concentrations and lactic acid were measured using a combination of enzyme kits (Megazyme) and high-performance liquid chromatography. Sugar (lactose, glucose, galactose) and lactic acid isomer concentrations were significantly different between the 2 commercial products, but neither product changed significantly during refrigerated storage. Each added sugar (10%) was stable throughout the 6-wk refrigerated storage period. The pH of all yogurts decreased slightly (−0.1 pH) during storage, but with no corresponding change in lactic acid concentration. These results provide foundational data on the stability of various sugars in cultured dairy products throughout refrigerated shelf life.